Lembaga dan Sistem Pendidikan Islam dalam Menyiapkan Persaingan Era 5.0 - Surawardi, Surawardi; Rahmasari, Devi; Rahmani, Dina; Halifah, Halifah (JURNAL PENDIDIKAN DAN KEWIRAUSAHAAN, 2024)
This research was conducted based on the urgency of Islamic education in the 5.0 era where all aspects of life are almost controlled by technology, so the role of Islamic education is needed in facing the challenges that may occur along with the times and technology. Therefore, this study aims to provide insights into how Islamic education should prepare everything to be ready to fight in this era. This research is library research which originates from various literature, both books and journals. The results of the study show that the human resources produced in education are decreasing because they prioritize technology, so Islamic education institutions and systems must be able to carry out various reforms that can maintain their existence in this 5.0 era.